Low Field MRI Measurements of the Normal Canine Trigeminal Nerve - Swain, Charlotte E.; Cherubini, Giunio B.; Mantis, Panagiotis (Frontiers in Veterinary Science, 2020)
There is no available measuring protocol and reference range for the normal canine trigeminal nerve. This can be problematic in cases of suspected bilateral trigeminal neuropathy since contralateral nerves cannot be a usefully compared. Trigeminal nerves and brain measurements were retrospectively assessed via multiplanar reconstruction (MPR) of 3DT1 post-contrast MR sequences from 137 dogs with no signs or diagnosis of trigeminal disease. Direct measurements of vertical brain height (BH), trigeminal nerves transverse height (TTH) and trigeminal nerves width in dorsal reconstruction (TDW) were made in a plane immediately caudal to the foramen ovale and used to derive trigeminal nerve-to-brain (NB) ratios, including height-to-brain ratio (HBR) and width-to-brain ratio (WBR). HBR (0.09, IQR=0.08-0.09) and WBR (0.10, IQR=0.09-0.11) maintained more consistent values across the study population compared to direct measurements of TTH (3.72, IQR=3.42-4.07) and TDW (4.37 +/- 0.63). Calculated normal reference intervals for HBR and WBR were 0.07-0.11 and 0.08-0.13, respectively and the largest NB ratios recorded in normal dogs were 0.13 and 0.14 for HBR and WBR, respectively. All measurements varied proportionally with weight, including HBR (r=0.41, p<0.0001) and small dogs had a significantly smaller HBRs compared to medium (p=0.0294), large (p<0.0049) and giant dogs (p<0.0044). Median HBR was the same across skull types (0.09), however post-hoc analysis detected significantly smaller HBRs in brachycephalic compared to mesaticephalic dogs (p=0.0494). In conclusion, trigeminal NB ratios may allow for accurate, objective assessment of the canine trigeminal nerves on MRI but further quantification of the effects of weight and skull type on suggested reference intervals is needed.